2022
DOI: 10.54393/pbmj.v5i1.281
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Patellofemoral Pain Syndrome Among Sports Sciences Students In Lahore

Abstract: Patellofemoral pain syndrome is characterized by severe pain around the knee cap during physical activities. Many researches have been done to describe the causes of PFP and it is found that it is multifactorial in nature. It is suggested that Patellofemoral pain can persist for many years and can cause decline in sports participation.  Muscular  imbalance and  over activity are major  causes of knee pain in Sports related PFP .Multiple management strategies are used in the intervention protocol of PFP  howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
1
0
0
Order By: Relevance
“…Out of the twenty workers who were exposed to the risk of PFPS, six males (30%) were affected (27) . While 63.54% of Lahore students reported mild or no symptoms of PFPS, 26.74% reported moderate symptoms of anterior knee joint pain, while 9.72% reported severe symptoms, our study's findings were consistent with those results, which were found by Ali et al (28) . Our findings are in line with those of research by Youssef et al (29) that found that young, active medical students at Cairo University were more likely to experience PFP in females than males .…”
Section: -Jobsupporting
confidence: 92%
“…Out of the twenty workers who were exposed to the risk of PFPS, six males (30%) were affected (27) . While 63.54% of Lahore students reported mild or no symptoms of PFPS, 26.74% reported moderate symptoms of anterior knee joint pain, while 9.72% reported severe symptoms, our study's findings were consistent with those results, which were found by Ali et al (28) . Our findings are in line with those of research by Youssef et al (29) that found that young, active medical students at Cairo University were more likely to experience PFP in females than males .…”
Section: -Jobsupporting
confidence: 92%
“…Strong awkwardness and over action are significant reasons for knee torment in Sports related PFP. 3 The AKP was formed as a result of a very wide range of events.…”
Section: Introductionmentioning
confidence: 99%